Industrial Revolution Era from Legal View in Indonesia In Relation to Business Competition 4.0 - Firmansyah Firmansyah; Yudho Taruno Muryanto (International Forum of Researchers and Lecturers, 2024)
Industrial Revolution 4.0 is revolutionizing the movement of the world economy. If you don't prepare yourself from now on, you will be far behind in the economic world. Government intervention in monopoly and oligopoly markets aims to influence prices, the quantity produced, and the distribution of income from economic activities. Intervention is carried out in 2 ways, namely: regulation and legal anti-monopoly. In this research, the recommendation is that the government must be able to make regulations that encourage the development of the digitalization economy as a strategy. Such as easy policies in financing startup businesses, tax incentives and guidance for SMEs. The government also needs to increase the development of telecommunications infrastructure in small areas so that it can minimize the imbalance that occurs.